Der Sozialstaat in Deutschland und Europa : Berichte und Diskussionen auf der Tagung der Vereinigung der Deutschen Staatsrechtslehrer in Jena vom 6. bis 9. Oktober 2004. (De Gruyter Recht, 2005)
[Publications from the Association of German Constitutional Law Teachers, Vol. 63]The volume reproduces the reports and discussions at the conference of the Association of German Constitutional Law Teachers in Jena from 6th to 9th October 2004.
Keywords: Public welfare -- Germany -- Congresses.; Public welfare -- Europe -- Congresses.; BUSINESS & ECONOMICS -- Economics -- Macroeconomics.; POLITICAL SCIENCE -- Economic Conditions.; LAW -- Constitutional.; LAW -- Public.; Public welfare.; Europe.; Germany.; Electronic books.; Conference papers and proceedings.